For this case we have the following system of equations:
![4x-12y = 0\\x + 3y = 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uhjapqw1l9atcadak2darzh5piutfc41d0.png)
To solve, we follow the steps below:
We multiply the second equation by -4:
![-4x-12y = -28](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dxtsadnld8vsd7jpix749rpgi1736idzbj.png)
We add the equations:
![4x-4x-12y-12y = 0-28](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v8rus0hzoibzgwvxt2g6k3r7nf6aq99qyp.png)
Equal signs are added and the same sign is placed.
![-24y = -28\\y = \frac {-28} {- 24}\\y = \frac {14} {12} = \frac {7} {6}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ult4q6lw08po0gjt1xfbfmav44pu0ta309.png)
We look for the value of the variable "x":
![x = 7-3y\\x = 7-3 \frac {7} {6}\\x = 7- \frac {21} {6}\\x = \frac {42-21} {6}\\x = \frac {21} {6}\\x = \frac {7} {2}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/np4t5ws0z8qcift7dx4u7bog2zype1nq4g.png)
Thus, the solution of the system is:
![(x, y): (\frac {7} {2}; \frac {7} {6})](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c9hy4cl2r54xwbef8d603uy16yycuhvj2u.png)
Answer:
![(x, y): (\frac {7} {2}; \frac {7} {6})](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c9hy4cl2r54xwbef8d603uy16yycuhvj2u.png)